IMPLEMENTASI KURIKULUM 2013 PENDIDIKAN ANAK USIA DINI (PAUD) DI SUMATERA SELATAN - Rahelly, Yetty (JPUD - Jurnal Pendidikan Usia Dini, 2018)
This research aims to find out the implementation of 2013 Curriculum for Early Childhood Education (ECE) in South Sumatra by using descriptive and qualitative methods. Data was collected by using interview, questionnaire, observation, and documentation. The data was analyzed by using triangulation technique through reduction, display, and verification. The result showed that the implementation of 2013 Curriculum for Early Childhood Education (ECE) began with the preparation of semester Planning learning tools (PROMES), Weekly Learning Plans (WLP), Daily Learning Implementation Plans (DLP), and Assessment Plans. The process of implementing learning with a scientific approach is done when stepping up before playing, playing activities, and communicating stages. Principals and teachers worked together in designing learning devices. Then, they discussed about themes, sub-themes and game ideas that are able to develop aspects of development in an integrated manner based on scientific approach. The assessments were carried out with authentic assessments such as observation, portfolio, performance and assignments. Before the learning process, the teachers were required to prepare daily lesson plans and learning media which will be used later in the learning process. Keywords: Early Childhood Education, 2013 Curriculum Implementation Penelitian ini bertujuan untuk mengetahui bagaimana implementasi Kurikulum 2013 PAUD di Sumatera Selatan dengan menggunakan metode deskriptif-kualitatif. Pengumpulan data dilakukan dengan wawancara, angket, observasi serta dokumentasi. Analisis data digunakan dengan teknik triangulasi melewati beberapa proses yakni reduksi data, penyajian data, dan penarikan kesimpulan/ verifikasi. Hasil penelitian menunjukkan implementasi kurikulum 2013 PAUD diawali dengan penyusunan perangkat pembelajaran Perencanaan Semester (PROMES), Rencana Pelaksanaan Pembelajaran Mingguan (RPPM), Rencana Pelaksanaan Pembelajaran Harian (RPPH), dan Perencanaan Penilaian. Proses pelaksanaan pembelajaran dengan pendekatan saintifik dilakukan saat pijakan sebelum main, kegiatan main, dan tahap mengkomunikasikan. Kepala Sekolah dan guru ikut bekerja sama dalam merancang perangkat pembelajaran. Kemudian, mereka mengkomunikasikan tema, subtema dan ide permainan yang mampu mengembangkan aspek perkembangan secara terpadu berbasis pendekatan saintifik. Penilaian yang dilakukan berupa penilaian otentik, misalnya observasi, portofolio, unjuk kerja dan penugasan. Sebelum proses pembelajaran guru juga diwajibkan untuk mempersiapkan RPP harian dan media pembelajaran yang nanti akan digunakan dalam proses pembelajaran. Kata Kunci : Implementasi Kurikulum 2013, Pendidikan Anak Usia Dini (PAUD)